Hydrops Fetalis and Persistent Pulmonary Hypertension in a Neonate with Anti-E Alloimmunization - Amit Sharma; Pournima Navalkele; Jagdish Desai; Prashant Agarwal (Case Reports in Obstetrics and Gynecology)
Anti-E alloimmunization is the third most common cause of neonatal hemolytic disease, typically causing mild to moderate hemolytic anemia. We report an unusual case of severe hydrops fetalis and persistent pulmonary hypertension (PPHN) in a neonate with anti-E alloimmunization. Our case emphasizes the importance of close surveillance for development of severe fetal hemolytic anemia and possible need for antenatal intervention. These neonates may also need vigilant monitoring for PPHN.